Exigências térmicas para a colheita e conservação pós-colheita de uvas apirênicas cultivadas no Vale do Submédio do Rio São Francisco - Santos, Ana Elisa Oliveira dos (Universidade Federal Rural do Semi-Árido, 2011)
This study aims at characterizing the phenological behaviour, thermal requirements and the ripening evolution of seedless grapes 'BRS Morena', 'BRS Clara' and 'BRS Linda' varieties, as well as improving techniques for postharvest storage according to the conditions of the Sub-middle São Francisco River Valley.Three experiments were carried in Petrolina, PE, in the 2010 harvest. Experiment I was aiming to identify the phenology, thermal requirements and the physical and physicochemical features in the harvest point. For this purpose, phenological periods were characterized, since pruning until early stage of budding, flowering, fruiting, ripening and harvesting, in addition to thermal requirements for each phase, expressed in degree-days. In the harvest point, it was also determined, the weight of the bunches, the diameter of the berries, the pulp firmness, the soluble solids (SS), titratable acidity (TA) and the pH. Due to the results obtained during the study period, the cycles of the vines from pruning and harvesting were 95 days and DG 1,449, for 'BRS Morena'; DG 1,497 and 97 days for 'BRS Clara', and 103 days and 1,592 DG to 'BRS Linda '. In general, the cultivars 'BRS Morena' and 'BRS Clara' had the physical and physicochemical potential for domestic and international marketing, provided that management practices are used to improve physical characteristics of these cultivars. Experiment II, in turn, aimed at monitoring the weekly progress of ripening. After the change of color of the berries, physical and physicochemical properties were assessed, with emphasis on bunch weight, berry diameter and length, pulp firmness, SS, TA, pH and skin anthocyanins. The last one held only for 'BRS Morena'. The evolution of the ripening of the grapes 'BRS Morena', 'BRS Clara' and 'BRS Linda' is characterized by significant increases in bunch weight, berry diameter and length, SS content, pH and anthocyanins, and decreases of acidity and pulp firmness, the harvest can be conducted from 95 days for cultivar 'BRS Morena'; 97 days for 'BRS Clara', and 103 days for 'BRS Linda'. Experiment III studied the influence of packaging associated with post-harvest cooling. In this experiment, the bunches were packaged in PET containers, plastic bags and contention plastic bags and packed in cardboard boxes, and then stored under refrigeration at 0 ± 1 º C and 83 ± 3% RH for 0, 15, 25 and 35 days. For each storage period, the bunches were evaluated for: weight loss, stalk quality, pulp firmness, SS and TA. In the specific conditions of this experiment, we recommend the use of plastic packaging, PET containers and plastic bags, associated with contention bags for the conservation of 'BRS Morena', 'BRS Clara' and 'BRS Linda' postharvest grapes
Harvest and postharvest of seedless grapes grown in the Middle São Francisco River Valley
Keywords: Vitis; seedless grapes; degrees-day; ripening; postharvest; Vitis; uvas apirênicas; graus-dia; maturação; pós-colheita; CIENCIAS AGRARIAS::AGRONOMIA::FITOTECNIA